2006
DOI: 10.1007/s11274-006-9299-x
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of kraft lignin by a newly isolated bacterial strain, Aneurinibacillus aneurinilyticus from the sludge of a pulp paper mill

Abstract: A kraft lignin-degrading bacterium (ITRC S 7 ) was isolated from sludge of pulp and paper mill and characterized as Aneurinibacillus aneurinilyticus by biochemical tests and 16SrRNA gene sequencing. The bacterium did not utilize kraft lignin (KL) as the sole source of carbon and energy. However, this strain reduced the color (58%) and lignin content (43%) from kraft lignin-mineral salt medium when supplemented with glucose at pH 7.6 and 30°C after 6 days. The degradation on addition of glucose in culture mediu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 34 publications
3
42
0
Order By: Relevance
“…Several researchers reported strains of Bacillus and Paenibacillus which displayed abilities to decolourize kraft black liquor [Chandra et al, 2007[Chandra et al, , 2008Hassan and Amr, 2009]. Moreover, Raj et al [2010] reported the decolourization of black liquor by a newly isolated bacterium, Aneurinibacillus aneurinilyticus. Incredibly, after 6 days of incubation, A. aneurinilyticus was able to reduce the colour of black liquor by 58% and the lignin content by 43% [Raj et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers reported strains of Bacillus and Paenibacillus which displayed abilities to decolourize kraft black liquor [Chandra et al, 2007[Chandra et al, , 2008Hassan and Amr, 2009]. Moreover, Raj et al [2010] reported the decolourization of black liquor by a newly isolated bacterium, Aneurinibacillus aneurinilyticus. Incredibly, after 6 days of incubation, A. aneurinilyticus was able to reduce the colour of black liquor by 58% and the lignin content by 43% [Raj et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Raj et al [2010] reported the decolourization of black liquor by a newly isolated bacterium, Aneurinibacillus aneurinilyticus. Incredibly, after 6 days of incubation, A. aneurinilyticus was able to reduce the colour of black liquor by 58% and the lignin content by 43% [Raj et al, 2010]. Similarly, Chandra and Abhisshek [2011] recently reported that mixed cultures of Citrobacter sp.…”
Section: Discussionmentioning
confidence: 99%
“…Among them most frequently studied fungus for these applications is basidiomycete P. chrysosporium and B. adusta, whose secreted enzymes have an enormous potential for decolorizing textile dyes [35][36][37]. Similarly, recent report shows that bacteria also able to produce the lignin peroxidase, which has ability to degradation of polymeric dyes from the textile industry and paper whitening through oxidative cleavage [12,19,20,23,38]. Where as, azoreductase is the key enzyme expressed in azo dye degrading bacteria that catalyze the reductive cleavage of the azo bond, which has been identified in several Values are mean of three experiments ± S.E.M.…”
Section: Enzyme Analysismentioning
confidence: 99%
“…The structure of natural lignin is very complex, and intact lignin is not commercially available. However, because of the similarities to natural lignin, kraft lignin (KL) has been widely used for lignin-related studies [13-17]. …”
Section: Introductionmentioning
confidence: 99%